Flesh flies (Diptera: Sarcophagidae) colonising large carcasses in Central Europe - Szpila, Krzysztof (Parasitol Res, 2015)
Sarcophagidae are an important element of carrion insect community. Unfortunately, results on larval and adult Sarcophagidae from forensic carrion studies are virtually absent mostly due to the taxonomic problems with species identification of females and larvae. The impact of this taxon on decomposition of large carrion has not been reliably evaluated. During several pig carcass studies in Poland, large body of data on adult and larval Sarcophagidae was collected. We determined (1) assemblages of adult flesh flies visiting pig carrion in various habitats, (2) species of flesh flies which breed in pig carcasses, and (3) temporal distribution of flesh fly larvae during decomposition. Due to species identification of complete material, including larvae, females, and males, it was possible for the first time to reliably answer several questions related to the role of Sarcophagidae in decomposition of large carrion and hence define their forensic importance. Fifteen species of flesh flies were found to visit pig carcasses, with higher diversity and abundance in grasslands as compared to forests. Sex ratio biased towards females was observed only for Sarcophaga argyrostoma, S. caerulescens, S. similis and S. carnaria species group. Gravid females and larvae were collected only in the case of S. argyrostoma, S. caerulescens, S. melanura and S. similis. Sarcophaga caerulescens and S. similis bred regularly in carcasses, while S. argyrostoma was recorded only occasionally. First instar larvae of flesh flies were recorded on carrion earlier or concurrently with first instar larvae of blowflies. Third instar larvae of S. caerulescens were usually observed before the appearance of the third instar blowfly larvae. These results contest the view that flesh flies colonise carcasses later than blowflies. Sarcophaga caerulescens is designated as a good candidate for a broad forensic use in Central European cases.